2011
DOI: 10.21608/mjae.2011.102606
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Characteristics of Corn Kernels

Abstract: The present study aimed to determine and recognize the physical ans mechanical properties as an important role in designing and developing of specific machines and their operations such as planting, harvesting and grading, Physical characteristics of corn kernels were obtained of two varieties: White Dent Corn single hybrid 10 (Corn 10), and yellow Dent Corn single hybrid 162, (Corn 162).For each of the physical characteristics, corn 10 gave the highest values comparing with corn 162. For each of the material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
(1 reference statement)
2
1
0
Order By: Relevance
“…But the "V2" length, width, and thickness recorded 10.02 ± 0.62 mm, 8.29 ± 0.65 mm, and 4.81 ± 1.03 mm, respectively as shown in (Table 1 and 2). There is a similarity between these results and the studies of Daboul et al (2011) for two classes of maize (single hybrid ( 10) and ( 162)), and El Fawal et al (2009) for two varieties of maize (hyb.310) and (hyb.352).…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…But the "V2" length, width, and thickness recorded 10.02 ± 0.62 mm, 8.29 ± 0.65 mm, and 4.81 ± 1.03 mm, respectively as shown in (Table 1 and 2). There is a similarity between these results and the studies of Daboul et al (2011) for two classes of maize (single hybrid ( 10) and ( 162)), and El Fawal et al (2009) for two varieties of maize (hyb.310) and (hyb.352).…”
Section: Resultssupporting
confidence: 74%
“…Also, it was observed that the smoother of structural surface, the lower recorded coefficient of static friction on the surface. These findings are comparable to those of the investigations of Daboul et al (2011) for two classes of maize single hybrid 10 and 162.…”
Section: Mechanical Properties Angle Of Reposesupporting
confidence: 89%
See 1 more Smart Citation